Incidence of pocket infection during long- term follow- up. (24th May 2021) - Vujadinovic, N; Radovanovic, NN; Milasinovic, G; Pavlovic, SU; Kircanski, B; Brankovic, N; Sajic, V; Milasinovic, A; Zivkovic, M; Bisenic, V
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction:  Cardiac implantable electronic devices (CIEDs) are being implanted worldwide in increasing numbers, so the incidence of hospitalizations due to their infections is also increasing.  Purpose: The aim of this study was to analyze the incidence of pocket infection related to the CIED procedure, as well as clinical presentation, diagnostic approach and methods of treatment during long-term follow- up on large cohort of patients. Methods: This was a retrospective, observational, single-center study. We enrolled patients who underwent CIED procedure between January 2011 and December 2015. The CIED procedure included implantation and replacement of the device. Pocket infection is defined as an infection limited to the generator pocket and can be presented from redness, swelling, pain to the skin erosion with exposure of the generator and/or leads. It may also be associated with lead infections and systemic CIED infections and/or infective endocarditis. All patients with CIED infection underwent the same diagnostics: complete blood count and inflammatory markers, pocket swab, three sets of blood cultures and echocardiography. Results: During the observed period 5 969 CIED procedures were performed (anti-bradycardia pacemakers 68.6%; ICD 21.4%; CRT-P/D 10.0%; CIED replacement 26.1%). CIED infection was registered in 41 patients (0.68%), most often after the ICD procedure (59.0%). In 22 patients (53.6%) the infection occurred after primo-implantation. The average time from intervention to infection was 17 ± 7.3 months. The mean follow-up was 52.2 ± 13.4 months. The most common manifestations of infection were redness (68.1%) and swelling (56.0%), then the protrusion of the generator or electrode (41.5%). Pacemaker pocket swabs and wound swabs were positive in 61.1% of samples and coagulase negative staphylococcus was found to be the most prevalent cause of infection (64.2%). The hemoculture test was positive in 10 patients, and the isolated causative agent matched the swab finding. The valvular vegetation was found in 4 patients. Pacemaker removal and surgical wound treatment were performed in all patients. Complete removal of all leads was achieved in 32 patients. In all pacemaker dependent patients and patients with ICD implanted in the secondary prevention of sudden cardiac death, reimplantation of the new device was performed in the same hospitalization on the opposite side. The remaining patients were operated on 3 to 4 weeks after the end of treatment.  Conclusions: It has been shown that the risk of pocket infection was low in a large number of patients, during long-term follow-up. The risk was higher in patients with ICD devices, and slightly higher after primo-implantation.